FUNCTION OF DISTANCE BETWEEN THE STRINGS BASED ON PIECEWISE CONSTANT MODEL - V. A. Prytkov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
A piecewise model of a string which allows to define a distance between two strings is proposed. The model can be applied to problems of fuzzy matching and text analysis and the model can be used with cyclic strings.